2007
DOI: 10.1002/mrd.20704
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of DNA‐demethylation in early mouse and rat embryos developed in vivo and in vitro

Abstract: Virtually all mammalian species including mouse, rat, pig, cow, and human, but not sheep and rabbit, undergo genome-wide epigenetic reprogramming by demethylation of the male pronucleus in early preimplantation development. In this study, we have investigated and compared the dynamics of DNA demethylation in preimplantation mouse and rat embryos by immunofluorescence staining with an antibody against 5-methylcytosine. We performed for the first time a detailed analysis of demethylation kinetics of early rat pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
3
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 28 publications
4
66
3
2
Order By: Relevance
“…After fertilization a rapid paternal-specific active demethylation is observed. Thereafter, there is a step-wise decline in methylation until the morula stage and the de novo methylation occurs at blastocyst stage [35,36]. In our experiments, the dynamic process of active demethylation of the paternal genome and de novo methylation at the blastocyst stage was detected in the control group and in the frozen sperm group ( Figure 2A1-F1 and a1-f1).…”
Section: Figuresupporting
confidence: 53%
See 1 more Smart Citation
“…After fertilization a rapid paternal-specific active demethylation is observed. Thereafter, there is a step-wise decline in methylation until the morula stage and the de novo methylation occurs at blastocyst stage [35,36]. In our experiments, the dynamic process of active demethylation of the paternal genome and de novo methylation at the blastocyst stage was detected in the control group and in the frozen sperm group ( Figure 2A1-F1 and a1-f1).…”
Section: Figuresupporting
confidence: 53%
“…First, in the pronuclear stage, the paternal genome undergoes active DNA demethylation, then the embryo maintains low DNA methylation status until the blastocyst stage when de novo methylation begins [32][33][34][35]. In the present study, we used a well-documented 5-methylcytidine antibody to visualize the methylation patterns during the different stages [32,36]. We found that the dynamic DNA methylation patterns in embryos from the fresh and frozen sperm groups were similar (Figure 2).…”
Section: Comparison Of Dna Methylation Patterns In Preimplantation Emmentioning
confidence: 66%
“…Though sometimes being variable in the degree of progression, the zygotic paternal demethylation seems to be common among mammals and is so far reported for mouse (Oswald et al, 2000;Rougier et al, 1998), rat (Dean et al, 2001;Zaitseva et al, 2007), human (Fulka et al, 2004), pig (Dean et al, 2001;, cattle (Dean et al, 2001), sheep (Hou et al, 2008) and rabbit (Lepikhov et al, 2008). Mouse zygotes serve as typical and relatively well characterized model to study epigenetic reprogramming in mammalian preimplantation embryos, therefore most of research data described and discussed here relate to the experiments on mouse embryos and gametes.…”
Section: Dna Methylation Reprogrammingmentioning
confidence: 99%
“…Active demethylation of the male pronucleus in rat zygotes proceeds with a slower kinetic than that in mouse embryo, and the rat zygotes at 16 hr after copulation still exhibited detectable methylation on the male pronucleus (Zaitseva et al, 2007). Fertilization of oocytes by spermatozoa with DNA damage induced by exposure to cyclophosphamide, an alkylating agent, 8.4 ± 0.6 4.0 ± 0.0 3.6 ± 0.4 5.6 ± 0.6 1/90 1/6 Control 7.2 ± 1.3 3.9 ± 0.2 3.5 ± 0.5 4.7 ± 1.0 3/62 2/7 GD0 8.6 ± 0.9 4.0 ± 0.0 3.8 ± 0.3 5.7 ± 0.2 0/53 0/5 GD1 8.6 ± 1.0 4.0 ± 0.0 3.7 ± 0.2 5.7 ± 0.3 1/44 1/5 GD2 7.8 ± 0.9 4.0 ± 0.1 3.6 ± 0.5 5.2 ± 0.9 1/40 1/4 GD3 8.2 ± 0.7 3.9 ± 0.1 3.6 ± 0.4 4.6 ± 1.4 3/50 2/5 GD4 7.4 ± 0.8* 3.8 ± 0. resulted in aberrant epigenetic reprogramming in the preimplantation rat embryo (Barton et al, 2005).…”
Section: Discussionmentioning
confidence: 93%